Estimates of the gross domestic product loss due to violence in Uganda. (1st March 2011) - Nakitto, M; Wandera, B; Cannoodt, L; Kiwanuka, N; Lett, R
Abstract : Introduction: There is lack of information on economic cost of violent related injuries in Uganda. The study estimates both direct and indirect costs incurred as a result of interpersonal and self directed violent injuries. Methods: Data were collected from four hospitals and two health centres (September 2008 to November 2009) using a standardised form while medico-legal data were collected from Government chemist and Police surgeon. Estimating cost parameters were derived from a WHO Manual. Statistical analyses were done using Stata 10. Results: Intentional injuries accounted for 20.7% of all injuries. Self-inflicted accounted for 30.3%, while interpersonal 69.7%. Violent injuries were frequent in homes; with causes: stabbing (31.1%) and poisoning (8.5%). Proportion of intentional injuries in homes was significantly higher than of unintentional injuries, 46.9% versus 23.7% (p<0.001). Direct total costs for self-directed injuries were 16 971 while per self-directed injury was 132.6. Indirect total costs for self-directed injuries were 506 443, while per self-directed injury was 3957. Direct medical costs for interpersonal injuries were 44 469, while 155 per interpersonal injury. Indirect costs for interpersonal injuries were 1 519 329, while 5312 per interpersonal injury. Direct costs due to violent injuries accounted for 0.04% of GDP while indirect costs accounted for 5.14% of GDP. Discussion and Conclusion: Economic cost of violent injuries in Uganda is substantive and could be saved for more pressing priorities if a preventive strategy is implemented.